온라인 상호작용 교수-학습 피드백 유형에 따른 TED 듣기과업 활동이 영어학습자의 듣기 이해도와 정의적 측면에 미치는 영향 - 차현지(Cha, Hyun Ji) (人文學硏究, 42(0), 2024)
본 연구의 목적은 온라인 상호작용 교수-학습 피드백 유형에 따른 TED를 활용한 듣기과업 활동이 한국 영어학습자의 영어 듣기 이해도와 정의적 측면에 미치는 영향을 알아보는 데 있다. 연구대상은 국내 수도권의 한 대학의 학술 교양영어 학습자를 대상으로 약12주간 걸쳐 비대면 온라인 상호작용 교수-학습 피드백 유형에 따라 실험 집단을 두 그룹으로 분류했다. 실험 집단 1은 동료 상호작용 피드백을 받는 집단으로 TED 연설을 듣고들은 내용을 요약하고 이를 영어로 말하기 활동을 했다. 실험 집단 2는 학습자 내적 상호작용 집단으로 TED 연설을 듣고 들은 내용을 요약하고 이를 영어로 말하기 활동을 했다. 약 12주간의 듣기 학습 동안 학습자는 온라인 채팅방에 듣기이해도 산출물인 말하기 요약파일을 제출했다. 약 12주간 학습자는 TED 듣기과업학습에서 내용에 대한 성찰, 본인 학습에 대한 자기 점검 등을 2회 이상을 학습저널형식으로 적어서 제출했다. 그 결과 동료들의 상호작용이 이루어지는 피드백을 받는 그룹과 내적 상호작용 그룹 모두 듣기 이해도에 유의미한 차이가 있었다. 이처럼 본 연구의 영어 듣고 영어로 요약하기 과업을 통한성취 경험으로 신입학 대학생이 긍정적인 학업 성취감을 느끼는 경험을 하는 계기가 되었다는 것이 본 연구의 의의이다. The purpose of this study is to investigate the impact of TED-based listening activities utilizing online interactive professor-student feedback types on the listening comprehension and affective aspects of English learners in Korea. The study targeted students of academic English courses at a university in the Seoul metropolitan area, classifying them into two groups over approximately 12 weeks based on non-face-to-face online interactive professor-student feedback types. Group 1 received peer-to-peer feedback, engaging in summarizing TED talks and speaking about them in English. Group 2 engaged in individual summarization and speaking tasks. Throughout the 12-weeks listening learning period, learners submitted speaking summary files, which served as their listening comprehension outputs, in an online chat room. Over the 12-week period, learners reflected on the content of TED listening tasks, self-checked their learning, and submitted entries at least twice in a learning journal format through a pre-designed online Naver survey. They also submitted listening tests and participated in surveys related to interactive teaching strategies and listening task learning. As a result, both the group receiving feedback through peer interaction and the group with internal interaction showed significant differences in listening comprehension. This study is significant because it allowed freshmen to experience a sense of accomplishment through tasks involving listening to English and summarizing it in English, thereby promoting positive academic achievement. KCI Citation Count: 0